Liability for Compensation of Insurance Parties for Maritime Transport Accidents Analysis Decision Number: 640/ Pdt.G /2014/PN.SBY - Valen Nainggolan; Gunardi Lie; Moody Rizqy Syailendra P (ARRUS Journal of Social Sciences and Humanities, 2024)
Trade becomes an important sector in the development of world economic. The focus of each country on establishing good relations occurs through cooperation in sending goods from one party to another. This research utilized a legal approach (statute approach through the studies obtained from the Shipping Law, Civil Code, Commercial Code, and Government Regulations. The delivery and transportation of goods that occurs is protected by another party called insurance. There are several responsibilities and risks faced during the transportation of goods, which aims to avoid out of control accidents. Insurance is a method used to protect and compensate for losses from goods damaged during transportation with insurance to minimize damage of goods during transportation.